2015
DOI: 10.1039/c4py01123f
|View full text |Cite
|
Sign up to set email alerts
|

Degradable cross-linked polymer vesicles for the efficient delivery of platinum drugs

Abstract: Nontoxic and acid-degradable polymer vesicles were synthesized as drug carriers. In vitro dose–response cytotoxicity studies suggested that the drug-loaded polymer vesicles were more efficient in delivering cis-platin into cancer cells compared to the internalization of the free drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 32 publications
(51 reference statements)
0
33
0
2
Order By: Relevance
“…The linear brush diblock copolymer poly(ONBAn n ‐ b ‐ONB‐PEG m ) (ONBAn n =oxanorbornenyl anhydride, ONB=ω‐oxanorbornenyl) synthesised by ring‐opening metathesis polymerisation self‐assembled into polymeric vesicles. The polymer bilayer was cross‐linked using an acid‐sensitive diamino ketal cross‐linker, and the anticancer drug cisplatin was conjugated in the bilayer . The cross‐linked vesicle protected the drug at physiological pH 7.4 and efficiently released the payload in the acidic lysosome with pH 5.5 (Figure ).…”
Section: Cross‐linked Polymer Nanocontainersmentioning
confidence: 99%
See 1 more Smart Citation
“…The linear brush diblock copolymer poly(ONBAn n ‐ b ‐ONB‐PEG m ) (ONBAn n =oxanorbornenyl anhydride, ONB=ω‐oxanorbornenyl) synthesised by ring‐opening metathesis polymerisation self‐assembled into polymeric vesicles. The polymer bilayer was cross‐linked using an acid‐sensitive diamino ketal cross‐linker, and the anticancer drug cisplatin was conjugated in the bilayer . The cross‐linked vesicle protected the drug at physiological pH 7.4 and efficiently released the payload in the acidic lysosome with pH 5.5 (Figure ).…”
Section: Cross‐linked Polymer Nanocontainersmentioning
confidence: 99%
“… Preparation of cross‐linked cisplatin‐conjugated vesicles. Reproduced with permission . Copyright 2015, Royal Society of Chemistry.…”
Section: Cross‐linked Polymer Nanocontainersmentioning
confidence: 99%
“…12,13 Even if the subject has been studied for over 15 years, new cases are still being published, with different crosslinking methods, such as radical reactions, [14][15][16][17] reversible disulde bonds, [18][19][20][21][22][23][24] or coupling reactions. [25][26][27][28][29][30][31][32][33][34][35][36] Original approaches have used uracyl moieties, 37 dopamine oxidation in the presence of air 38 or cinnamate reversible dimerization. 39 More sophisticated systems present a crosslinking enabling the release of the drug with adequate physiological conditions (presence of dithiothreitol or glutathione, difference of pH).…”
Section: Introductionmentioning
confidence: 99%
“…39 More sophisticated systems present a crosslinking enabling the release of the drug with adequate physiological conditions (presence of dithiothreitol or glutathione, difference of pH). 18,[21][22][23][24][25]27,34,35,[40][41][42] Interestingly, Rajdev showed that Hbonding between hydroxyl groups in poly(hydroxyethyl methacrylate) could be used as supramolecular crosslinking. 43 The same concept could be suggested for micelles exhibiting a large amount of p-p stacking.…”
Section: Introductionmentioning
confidence: 99%
“…For example, drug carriers formed via self-assembly of amphiphilic block copolymers in aqueous solutions, such as micelles and vesicles, have been proposed. [10][11][12][13][14] Although covalent stabilization of micelles and vesicles has been attempted to prevent their dissociation, [15][16][17] this introduces additional complexity. A change in environmental conditions allows manipulation of the size and morphology of these aggregates, besides the molecular weight and block length ratios of the copolymers, which are easily tuned.…”
Section: Introductionmentioning
confidence: 99%